Implementasi Customer Experience PT PGN Area Bekasi Dalam Membangun Brand Awareness - Yurika Dita Pratiwi; Jamiati KN (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
People today form their opinions based on their experiences interacting with brands. Experience is the main aspect to win the hearts of consumers. The aim of this research is to find out how the implementation of Customer Experience through the City Gas Tour event carried out by PT Perusahaan Gas Negara Bekasi Area builds brand awareness. As well as to find out the inhibiting and supporting factors in the City Gas Tour event in building brand awareness. Using Pelsmacker, Geuen, Van De Bergh's brand activation dimension theory. Using a Qualitative Approach with Descriptive methods. Data collection techniques through Semi-Structured Interviews. Test the validity of the data using the Source Triangulation technique for participants attending the 2022 City Gas Tour event and also Customer Experience Specialists. The results of the research are that the dimensions that play an important role are Sense, Think and Act. The sense dimension by taking a direct approach through various striking facilities; dimensions related to activating Instagram social media and making broadcasts via WhatsApp blast to local residents at the event point; think by inviting participants to think from staff explanations through the question and answer booth provided; Take action by taking direct action to experience the facilities. The inhibiting factors are the underutilization of social media and the lack of conduciveness to the event due to interference with vehicle traffic and the volume of people's voices. The supporting factor is natural gas products from PGN which guarantee that the gas will be distributed 24 hours. Also, the location where the event takes place, by holding an event in the middle of a crowd, you can attract people to visit this event.